Monoclonal Antibodies Specific to Water Buffalo (Bubalus bubalis) Myxovirus Resistance Protein_1 - Phai, Dam Van; Anne-Sophie, Van Laere; Axel, Dubois; Dao, Bui Tran Anh; Daniel, Desmecht (Journal of Buffalo Science, 2020)
Recombinant bubaline (Bubalus bubalis) myxovirus resistance protein 1 (bbMx1) was successfully expressed by an Escherichia coli expression system. After immunization and cell fusion, a set of ten mouse hybridomas producing mAbs to bbMx1 was established. The ten corresponding mAbs were further characterized using indirect ELISA, western blot analysis and immunocytofluorescent staining. Eight mAbs, designated 11C7, RD5, NF3, 9D1, FD4, PE6, 11A7 and 10F5, displayed binding abilities and specificity in the three formats. Moreover, combining NF3 (for capture) with RD5 (for detection), 9D1 with RD5, FD4 with 11C7 or PE6 with 11C7 generated a strong signal in a prototype sandwich-ELISA. The results suggest that the mAbs developed and characterized here provide an excellent starting point for developing diagnostic tools aimed at detecting viral infections in the water buffalo, whatever using immunoblotting, immunocytostaining or sandwich-ELISA.